Penegakan Hukum Terhadap Pasien Covid-19 Yang Melakukan Perlawanan Protokol Kesehatan - Boy Maulany; Elsa Rina Maya Toule; Carolina Tuhumury (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Law Enforcement Against Covid-19 Patients who oppose health protocols is urgently needed considering the flight of Covid-19 patients with status (PDP) is very dangerous, because Corona virus disease 2019 (covid-19) is a contagious disease so that fast preventive action is needed from the government. Indonesia. In responding to this, the Indonesian government uses Law Number 6 of 2018 concerning Health Quarantine, to take preventive and handling measures against the entry or exit of disease. However, resistance to health protocols is still being carried out by the Indonesian people, especially Covid-19 patients.Purposes of the Research: Aims to analyze and discuss Covid-19 patients who oppose health protocols, can be held criminally accountable and law enforcement against Covid-19 patients who oppose health protocols. The method used in this paper is a normative legal research method. The legal materials used are primary, secondary and tertiary legal materials. Methods of the Research: In this legal research, the author uses normative research. Normative research is library research, where in normative research library materials are data sources which are classified as secondary data in research. Secondary data has a broad scope, ranging from personal letters, book, to afficial documents issued by the government.Results of the Research: The results showed that Covid-19 patients who violated the health protocols set by the government could be subject to sanctions as a form of criminal liability. Thus, for Covid-19 patients who violate the provisions of the applicable laws and regulations, the authorities can take firm action by imposing sanctions in accordance with the provisions of the applicable regulations.